Central bank transparency and inflation (volatility): New evidence - Christoph S. Weber (Friedrich-Alexander-Universität Erlangen-Nürnberg, Bavarian Graduate Program in Economics (BGPE), 2016)
The last decades have shown a tendency towards higher central bank transparency. It became customary for central bankers to explain their monetary policy decisions in detail and for them to publish inflation forecasts. This leads to the question of how central bank transparency is entangled with price stability and inflation volatility. A plethora of studies analysed the relationship from a theoretical point of view and came to contradictory results. Whilst some studies argued that transparency leads to lower inflation, others concluded that openness of central banks results in higher prices. Conversely, there is only a small amount of studies looking at this issue empirically. Most studies found a diminishing effect of transparency on inflation. However, these studies hardly controlled for other causes of inflation. This paper tries to close this gap by employing a panel data set on central bank transparency. We find that transparency significantly reduces inflation rates even if we control for other determinants of inflation. This result still holds under various robustness checks. The same is true for inflation volatility: central bank transparency seems to diminish inflation uncertainty. This confirms the economic importance of central bank transparency.
Keywords: E31; E42; E58; 330; Central Bank Transparency; Inflation; Inflation Volatility; Determinants of Inflation; Central Bank Independence